2014
DOI: 10.1111/1574-6968.12471
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to eliminateWolbachiainfections inNasonia vitripennisrevealed different antibiotic resistance between two bacterial strains

Abstract: Wolbachia are widespread in insects and can manipulate host reproduction. Nasonia vitripennis is a widely studied organism with a very high prevalence of Wolbachia infection. To study the effect of Wolbachia infection in Nasonia spp., it is important to obtain noninfected individuals by artificial methods. Current methods that employ sugar water-containing antibiotics can successfully eliminate Wolbachia from the parasitic wasps; however, treatment of at least three generations is required. Here, we describe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The N. vitripennis populations were the Hangzhou strain (from the Gongyin Ye lab, ZheJiang University) (Zhang et al, 2005) infected with Wolbachia supergroup A (Liu et al, 2014). The housefly larvae were fed bran for 5–6 days until pupation.…”
Section: Methodsmentioning
confidence: 99%
“…The N. vitripennis populations were the Hangzhou strain (from the Gongyin Ye lab, ZheJiang University) (Zhang et al, 2005) infected with Wolbachia supergroup A (Liu et al, 2014). The housefly larvae were fed bran for 5–6 days until pupation.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that Wolbachia could be removed by feeding insects sugar water containing antibiotics, but the complete elimination of Wolbachia required at least three to six successive generations of antibiotic treatment [ 39 , 40 , 41 ]. Liu et al [ 42 ] described a novel approach to eliminate Wolbachia from Nasonia vitripennis by feeding pupae with rifampicin to two generations. Therefore, different antibiotics and methods could be used to try to eliminate Wolbachia from T. pretiosum in further research.…”
Section: Discussionmentioning
confidence: 99%
“…The similar approach was used in previous studies of Wolbachia diversity in parasitic wasp Nasonia vitripennis (Liu et al . ) or in terrestrial heteropteran bugs (Kikuchi & Fukatsu ). Here, we found that Wolbachia infecting A. aestivalis belongs to supergroup A.…”
Section: Discussionmentioning
confidence: 99%